Response of Increasing NaCl Concentrations on Growth and Proline Content of Tacca leontopetaloides cultured in vitro - Martin, Andri Fadillah; Hapsari, Betalini Widhi; Ermayanti, Tri Muji (Annales Bogorienses, 2015)
The effects of increasing NaCl concentrations on growth and proline content of Tacca leontopetaloides cultured in vitro were investigated. T. leontopetaloides were suspected to have high tolerance against salinity, thus the purpose of this research was to investigate the effect of increasing NaCl concentrations added on growth medium on growth and proline content of T. leontopetaloides grown in vitro. In vitro corms were cultured on MS medium supplemented with NaCl at concentrations of 0, 10, 25, 50, 75, 100, 150 and 200 mM, respectively. After six weeks in culture, shoots height, shoots number, leaves number, fresh weight, as well as their proline content were recorded. The results showed that fresh weight of shoots grown on MS medium supplemented with 10, 25 and 75 mM NaCl was higher compared to the control treatment. Fresh weight decreased when shoots were cultured on MS medium supplemented with NaCl at more than 100 mM. Proline content increased along with the increase of NaCl concentrations. Meanwhile, the height of shoots, number of shoots, and number of leaves decreased along with the increase of NaCl concentrations.